The people and the nation populism and ethno-territorial politics in Europe - Heinisch, Reinhard 1963-; Massetti, Emanuele; Mazzoleni, Oscar (Routledge studies in extremism and democracy, 2020)
"The edited book brings together country experts on populism, ethno-territorial politics and party competition. The book consists of twelve empirical chapters, covering seven Western European states (Austria, Belgium, France, Italy, Spain, Switzerland, and the UK) as well as four Central-European states (Croatia, Hungary, Serbia and Poland). It is a collaboration by scholars from across Europe which contributes to the growing literature on populism by focusing on a relatively unexplored research agenda; the intersection on territoriality, ethno-politics and populism. Presenting an original perspective contributing experts use case studies to highlight the territorial dimension of populism in different ways and identify that a deeper understanding of the interactions between populist actors and ethno-territorial ideologies is required. This book will be of interest to academics, researchers and students of European politics, populism and ethno-territorial politics"--